German language teaching and sustainability – approaching theory and practice - Voerkel, Paul; Zhong, Xingyu (Journal for German and Scandinavian Studies / Списание „Германистика и скандинавистика“, 2025)
The concept of sustainability is constantly evolving and is therefore having an impact on teaching and its content, meaning that the discussion about its significance for society and education is always necessary and relevant. In this context, this article discusses how sustainability can be integrated into foreign language teaching as a meaningful subject of knowledge in order to promote current teaching approaches. To this end, the origins of the term sustainability and its development into the concept we know today are explained. Two examples will then be used to show how sustainability can be integrated into the initial and in-service training of teachers of German as a foreign language. One of the greatest challenges is the development of educational and teaching competences with regard to sustainable development. Based on theoretical assumptions and practical examples, various possibilities are shown for teaching foreign languages from a new perspective and thus organising learning in a meaningful and context-related way.